Factors Affecting Economy of Khyber Pakhtunkhwa. - Muhammad, Imranullah (2017)
The financial system spurs the economic growth or economic growth necessitates the development of financial system is a million dollar question. Many studies across the globe have been undertaken to find an amicable solution with different degrees of success. This study abridged the gap between knowledge in the current literature to address the specific problem of resolving the economic problems and bringing uplift to the economy of Khyber Pakhtunkhwa by suggesting appropriate measures and measuring the impact of political, religious, economic and cultural factors on perceived economic growth. Survey questionnaires have been used to record responses from respondents to gain insight into their political, religious, cultural and economic perceptions. The study relied on convenience sampling and utilized structural equation modeling technique to test the measurement and structural models to represent relationship among latent variables or constructs. The results of hypotheses tests for overall model revealed an insignificant impact of Perceived Cultural Stability and Perceived Religious Affiliation on Perceived Economic Growth while Perceived Economic Environment and Perceived Political Stability had a significant impact on Perceived Economic Growth. Though the study is limited to evaluation of how different factors impact the perception of economic growth, future studies may evaluate the same from a wider perspective. Furthermore, future studies may also involve other factors that could potentially influence the economic growth. The study was limited to Khyber Pakhtunkhwa; future studies to validate the findings of the present study may be conducted in other regions also. Keywords: Financial Systems, Perceived Political Stability, Perceived Cultural Stability, Perceived Religious Affiliations, Perceived Economic Growth. The financial system in Pakistan is made up of the State Bank of Pakistan, all scheduled banks, financial institutions regulated by the Security & Exchange Commission of Pakistan (SECP), Directorate of National Savings, Micro Finance Institutions (MFI’s), remittances sent or received through legitimate chartered exchange companies, Pakistan Post Office Directorate, Insurance companies, money dealers in the private sector, kinship, acquaintances, merchants and traders and dealers operating in the rural areas (Mehrteab, 2005). Countries in the South Asian hemisphere in particular are under the tremendous influence of economic slump but the situation in war torn areas like Khyber Pakhtunkhwa is even worse. The Khyber Pakhtunkhwa province in Pakistan is one of those areas which are badly affected by the war-like situation and terrorism. According to the Economic Survey of Pakistan, the KP Province is contributing 13 % to the GDP of the country as against a total population of 27 million which amounts to 14 % of the total population of Pakistan. Majority of the people living in KP Province